2009
DOI: 10.1016/j.biortech.2008.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Determination of thermal properties of composting bulking materials

Abstract: Thermal properties of compost bulking materials affect temperature and biodegradation during the composting process. Well determined thermal properties of compost feedstocks will therefore contribute to practical thermodynamic approaches. Thermal conductivity, thermal diffusivity, and volumetric heat capacity of 12 compost bulking materials were determined in this study. Thermal properties were determined at varying bulk densities (1, 1.3, 1.7, 2.5, and 5 times uncompacted bulk density), particle sizes (ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 28 publications
5
49
0
3
Order By: Relevance
“…3). Cette élévation de la température est la conséquence directe de l'oxydation de la matière organique des substrats (Hassen et al, 2001 ;Ahn, 2009). Cette oxydation permet ainsi la libération de l'énergie contenue dans les liaisons chimiques des molécules constitutives (Ryckeboer, 2003).…”
Section: Résultats Et Discussion Evolution De La Températureunclassified
“…3). Cette élévation de la température est la conséquence directe de l'oxydation de la matière organique des substrats (Hassen et al, 2001 ;Ahn, 2009). Cette oxydation permet ainsi la libération de l'énergie contenue dans les liaisons chimiques des molécules constitutives (Ryckeboer, 2003).…”
Section: Résultats Et Discussion Evolution De La Températureunclassified
“…Water holding capacity was measured using a modified Hilgard method [20,21]. Bulk density and free air space (FAS) were measured using a method reported by Ahn et al [22]. Total carbon (TC) and total nitrogen (TN) contents were analyzed using an elemental analyzer (2400 CHNS/O series II system, Perkin Elmer, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In BM, compaction and higher than optimal (60%) moisture content (Table 1) resulted in anaerobic areas, which resulted in reduced pile temperatures and/or microbial activity. Ahn et al (2009) reported a greater thermal conductivity (W m −1 K) and thermal diffusivity (mm 2 s −1 ) of WS compared with BM, whereas the volumetric heat capacity (MJ m −3 K) was greater. This suggests that heat retention in BM could be expected to be greater than WS, meaning that the pile temperatures observed over the duration of the study were a result of microbial activity and not the insulation properties of the compost materials.…”
Section: Composting Processmentioning
confidence: 91%